2021
DOI: 10.1186/s40510-021-00353-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of images posted to social media by orthodontists on public perception of professional credibility and willingness to become a client

Abstract: Background Many patients choose health professionals using the Internet, whether through websites or social media. In orthodontics, an orthodontist’s relationship with active and potential patients can be affected by social media interactions, both as a marketing tool and as a tool for providing educational information. The purpose of the present study was to analyze the public perception of professional credibility and willingness to become a client, based on images posted by orthodontists on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…Surprisingly, this issue is still so prevalent [ 48 ]. Patients search on the web for their physicians and their impressions about professionalism are based on the publicly available web-based SM content [ 68 , 69 ], but patients also use SM as the most influential web-based method in selecting a physician [ 69 , 70 ]. Besides patients, publicly available content on SM is also screened by future or current employers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, this issue is still so prevalent [ 48 ]. Patients search on the web for their physicians and their impressions about professionalism are based on the publicly available web-based SM content [ 68 , 69 ], but patients also use SM as the most influential web-based method in selecting a physician [ 69 , 70 ]. Besides patients, publicly available content on SM is also screened by future or current employers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Meira et al [ 164 ] investigating professionalism perception of orthodontist through exposure of laypeople, dental students, and dentists to images usually found on Instagram found that images related to social and family relationships were associated with lower scores regarding the perception of professional credibility for all groups [ 164 ]. They argued that their results indicate that personal images, possibly because they are not related to the professional context, contribute little toward the professional image of orthodontists on Instagram.…”
Section: Discussionmentioning
confidence: 99%
“…Os temas mais discutidos em relação à aplicação ética da Internet e das tecnologias de comunicação na área da saúde são privacidade do paciente, confidencialidade e anonimato, segurança de dados, concorrência leal e propaganda real. No entanto, os princípios de ética e o código de conduta profissional de cada país devem primeiro ser respeitados (Meira et al, 2021).…”
Section: Discussionunclassified
“…Por isso, a ética, sendo um conjunto de valores e princípios que possibilitam a interação harmoniosa e respeitosa entre diferentes pessoas desconsiderando interesses individualistas e enganosos, deve ser aplicada em sua totalidade de intervenções de marketing para benefício do empreendimento odontológico e dos pacientes (Meira et al, 2021). sociais online não infringem a lei nem desrespeitam os princípios éticos e considerando, portanto, a flexibilidade, amplo alcance, facilidade de uso e baixo custo, quando comparados aos meios tradicionais, desistir de usá-los ou se opor ao seu uso seria imprudente (Meira et al, 2021).…”
Section: Discussionunclassified